Prompt and non-prompt J / ψ and ψ ( 2 S ) suppression at high transverse momentum in 5.02 TeV Pb+Pb collisions with the ATLAS experiment - Aaboud, M; Aad, G; Abbott, B; Abdinov, O; Abeloos, B; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abulaiti, Y; Acharya, B S; et al. (The European physical journal. C, Particles and fields, 2018)
A measurement of J / ψ and ψ ( 2 S ) production is presented. It is based on a data sample from Pb+Pb collisions at s NN = 5.02 TeV and pp collisions at s = 5.02 TeV recorded by the ATLAS detector at the LHC in 2015, corresponding to an integrated luminosity of 0.42 nb - 1 and 25 pb - 1 in Pb+Pb and pp, respectively. The measurements of per-event yields, nuclear modification factors, and non-prompt fractions are performed in the dimuon decay channel for 9 < p T μ μ < 40 GeV in dimuon transverse momentum, and - 2 < y μ μ < 2 in rapidity. Strong suppression is found in Pb+Pb collisions for both prompt and non-prompt J / ψ , increasing with event centrality. The suppression of prompt ψ ( 2 S ) is observed to be stronger than that of J / ψ , while the suppression of non-prompt ψ ( 2 S ) is equal to that of the non-prompt J / ψ within uncertainties, consistent with the expectation that both arise from b-quarks propagating through the medium. Despite prompt and non-prompt J / ψ arising from different mechanisms, the dependence of their nuclear modification factors on centrality is found to be quite similar.